Comparison of a new air‐assisted sprayer and two conventional sprayers in terms of deposition, loss to the soil and residue of azoxystrobin and tebuconazole applied to sunlit greenhouse tomato and field cucumber. Issue 2 (2nd November 2017) - Li, Yanjie; Li, Yifan; Pan, Xiang; Li, Qing X; Chen, Ronghua; Li, Xuesheng; Pan, Canping; Song, Jianli
Abstract: BACKGROUND: Plant protection products (PPPs) are applied in China and many other developing countries with knapsack sprayers at high volumes with coarse spray quality, resulting in a high percentage of pesticide losses. In this study, a new air‐assisted electric knapsack sprayer and two conventional knapsack sprayers were evaluated in terms of pesticide deposition, residues and loss into the soil. Artificial targets fixed to the upper side and underside of the leaf surface in six zones (at two depths and three heights) were used to collect the deposition, which were analyzed by liquid chromatography triple‐quadrupole mass spectrometry. RESULTS: The air‐assisted electric knapsack sprayer produced more deposition and better penetrability and uniformity than the two traditional spraying methods. In particular, the air‐assisted electric knapsack sprayer reduced pesticide losses to the soil by roughly 37% to 75% and deposited 1.18 and 1.24 times more pesticide than the manual air‐pressure and battery‐powered knapsack sprayers, respectively. The residues of azoxystrobin and tebuconazole in tomato and cucumber were below the maximum residue limits (MRLs). CONCLUSION: In general, use of the the air‐assisted electric knapsack sprayer in tomato and cucumber crops could improve the effectiveness of PPPs, reduce the risk of contamination and protect food safety. © 2017 Society of Chemical Industry Abstract : Comparing air‐assisted electric knapsack sprayer with battery‐powered knapsack sprayer and manual air‐pressure knapsack sprayer, in greenhouse and open fields, for spray deposition and distribution, loss to soil, pesticide efficiency, and pesticide residues.